Dual in vitro and in silico analysis of thiacalix[4]arene dinaphthalene sulfonate for the sensing of 4-nitrotoluene and 2, 3-dinitrotoluene. (24th January 2018) - Modi, Krunal; Panchal, Urvi; Patel, Chirag; Bhatt, Keyur; Dey, Shuvankar; Mishra, Divya; Jain, V. K.
Abstract : A newly synthesized thiacalix[4]arene dinaphthalene sulfonate, i.e., TCDNS, has been used as a fluorescence quencher for 2, 3-DNT as well as 4-NT. The complex was analyzed by ESI-MS and 1 H-NMR titration, which has been further confirmed by the in silico study. Abstract : A new fluorescent thiacalix[4]arene dinaphthalene sulfonate (TCDNS) was synthesized by a reaction of thiacalix[4]arene with naphthalene sulfonyl chloride. TCDNS was characterized by 1 H-NMR, 13 C-NMR, and ESI-MS spectrometric analyses. The selectivity of fluoroionophore was analyzed for 4-nitrotoluene (4-NT) and 2, 3-dinitrotoluene (2, 3-DNT) among various nitroaromatic compounds (NACs) using the spectrofluorimetric technique. 4-NT and 2, 3-DNT behave as the strong emission quenchers for TCDNS. The information about the complexation of TCDNS with 4-NT and 2, 3-DNT was revealed by ESI-MS and 1 H NMR analysis. A standard addition method was used for the detection of 4-NT and 2, 3-DNT in a water sample. The complex formation in the cases of TCDNS⊃4-NT and TCDNS⊃2, 3-DNT has been demonstrated by molecular docking and dynamics simulation techniques.